(untitled) (SAARC Journal of Agriculture, 2014)
A field experiment was conducted during rabi 2007-08 to 2008-09 at Uttar Banga Krishi Viswavidyalaya, Cooch Behar situated at sub-Himalayan plains popularly known as terai region of West Bengal, India to study the productivity of yellow sarson under different nutrient management practices and seed priming methods. The experiment was laid out in a factorial randomized block design with eight nutrient management practices and three seed priming methods. The results showed marked improvement in yield components, productivity and economics of yellow sarson due to integrated nutrient management and seed priming methods. Significantly highest seed yield (1374 kg ha-1) was recorded with combination comprising FYM + Azotobacter + PSB and 75% of the recommended fertilizers. The integrated nutrient management practice also had greater impact in production economics, sustenance in soil fertility and enrichment of soil nutrients. The crop receiving plant nutrients only from chemical sources showed poor productivity leading to less remuneration. Higher seed oil content (41.8% and 42.2%) was obtained with the application of 100% of the recommended dose (60:30:30 kg N:P2O5:K2O kg ha-1) along with sulphur (20 kg ha-1) but the oil yield was not impressive due to poor seed yield. Pre-sowing soaking of seeds with 100 ppm KH2PO4 also showed improvement in yield components, productivity and oil yield of the yellow sarson crop compared to seeds soaked with 100 ppm Na2HPO4 and water. Net returns and return/rupee invested were higher when the yellow sarson seeds were soaked with 100 ppm KH2PO4 over the other soaking methods. Variations in residual fertility were not discernible due to seed soaking. DOI: http://dx.doi.org/10.3329/sja.v12i1.21117 SAARC J. Agri., 12(1): 106-116 (2014)